HRM philosophies and policies in semi-autonomous agencies: identification of important contextual factors. Issue 18 (11th October 2021) - Blom, Rutger; Kruyen, Peter M.; Van Thiel, Sandra; Van der Heijden, Beatrice I. J. M.
Abstract: Although a contextual perspective in HRM research has been strongly advocated, empirical evidence on how context shapes HRM is still lacking. This study explored HRM philosophies and policies in Dutch semi-autonomous government agencies and how they are shaped. These agencies were given considerable autonomy by central government with regard to their HRM philosophies and policies in order to make more effective use of their human capital. Based on our findings from thirty semi-structured interviews with HRM managers, we identified that (a) facilitation philosophies are dominant, while accumulation philosophies are less present and utilization philosophies nonexistent; (b) mixed philosophies are present in some cases; (c) ability- and motivation-enhancing policies are dominant, while opportunity-enhancing policies are less present; (d) similarities in HRM are strongly shaped by external factors; and that (e) differences in HRM are strongly shaped by internal factors.